(untitled) (Fiep Bulletin - online, 2017)
The physical activity helps maintain a healthy body and stimulates social interaction promoting quality of life.Thus, the study aimed to evaluate the development of the physical health of the elderly, using the water activities as the means ofobservation of effects and benefits of this activity, to be one of the most currently used by this population. The research is a Workof Course (TCC) in Academic Physical Education Luiz Paulo Papini da Silva, and is the product of an investigation whose aim is tosolve problems and address questions through the use of scientific procedures. Thus, based on the general objectives of theresearch, as classification criteria, it can be said that this is an exploratory research, because it leads to a study with the purpose of familiarizing the proposers to the subject, in order to make it more explicit or build hypotheses about that reality that isproposed. Although it has traces of explanatory research, here it is intended to analyze the data collected, with the scope toidentify, interpret and discuss the benefits achieved by the practice of water activities for the elderly.